2005
DOI: 10.1002/gps.1407
|View full text |Cite
|
Sign up to set email alerts
|

Why and how antipsychotic drugs are used in 40 Sydney nursing homes

Abstract: In Sydney in 2003, most (80%) of the nursing home residents for whom antipsychotics were prescribed did not have a diagnosis of schizophrenia. The records suggested that insufficient attention had been given to the possibility that use of certain antipsychotics can be associated with impaired glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
(22 reference statements)
5
20
0
1
Order By: Relevance
“…residents was comparable to previous Australian and international studies (Snowdon et al, 2005;Bronskill et al, 2004). There was a significant use of atypical antipsychotic medications (79.5%) compared to the use of conventional antipsychotics (20.5%).…”
Section: Discussionsupporting
confidence: 90%
“…residents was comparable to previous Australian and international studies (Snowdon et al, 2005;Bronskill et al, 2004). There was a significant use of atypical antipsychotic medications (79.5%) compared to the use of conventional antipsychotics (20.5%).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the overall rate seems to have changed little in the last twenty years. Our national rate is similar or lower than rates reported in larger international studies in care homes in the US, Canada, Sweden, Finland, Switzerland and Australia and confirms that antipsychotic prescribing in care homes is not a parochial problem for the UK healthcare system but a challenge for all developed populations (Kamble et al, 2008;Lövheim et al, 2008;Rochon et al, 2007;Snowdon et al, 2005;Feng et al, 2009). Community prescribing is less well described and gender, regional and socio-economic differences have not been examined before.…”
Section: Discussionsupporting
confidence: 85%
“…However, this finding concurs with earlier studies on older schizophrenic residents in nursing homes, where 15-19% were not receiving antipsychotic medication (Bowie et al, 2001;Snowdon et al, 2005). Harvey et al (1999) found that nursing home residence was associated with more severe negative and cognitive, as well as greater functional impairment than among community dwellers and psychiatric inpatients.…”
Section: Discussionsupporting
confidence: 89%